Keterampilan Metakognitif Peserta Didik Dalam Menyelesaikan Masalah Matematis Bentuk Soal Cerita - Nizar Mahar Dhika Ismail; Dori Lukman Hakim; Hanifah Nurus Sopiany (JP3M (Jurnal Penelitian Pendidikan dan Pengajaran Matematika), 2022)
This article discusses the metacognitive abilities of students in solving mathematical problem solving story problems. This study uses a qualitative approach by using the case study method. Research subjects were selected by purposive-sampling. The subjects were six people, taken from 38 students, to represent mathematics ability with low, medium, and high categories of 2 people each. This study uses a test instrument of mathematical problem solving story questions, a metacognitive ability questionnaire, and an interview guide. The data were collected using the technique of giving tests, giving questionnaires, and interviewing guidelines. The data analysis technique used consists of 3 stages, namely analyzing the results of students' answers, presenting the results of data analysis, and making conclusions from the results of data analysis of students' mathematical problem solving abilities. The results of this study indicate that based on the results of tests on students with high mathematical abilities, they are able to carry out the three stages of metacognitive abilities, namely planning, monitoring, and evaluating. The students with moderate mathematical abilities, the results of the study showed that they were able to carry out the planning, and monitoring stage but had not been able to carry out the evaluating stages. Meanwhile, students with lower category mathematics abilities have not been able to carry out the three stages of metacognitive abilities, namely planning, monitoring, and evaluating.